PENANDA EMOTIF PARTIKEL JONEGOROAN - Mixghan Norman Antono (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research is a qualitative study conducted to reveal the emotive markers of particles used by the Jonegoroan Subdialek Language. At least this subdialect has seven particles, including: (1) –leh, (2) –je, (3) –jal, (4) –jan, (5) –em and –nem, (6) –nyo, and ( 7) -men. . Each particle has a different emotive marker. When classified, the use of particles in the Jonegoroan subdialect serves to mark the emotive affirmation, disappointment, overload, ownership, and statement of the negationKeywords: Particle, Jonegoroan Subdialek, emotive marker